State of development of public administration in conditions of humanization tendencies - Васильківська, Вікторія Владиславівна; Васильківська, В. В.; Васильковская, Виктория Владиславовна; Vasylkivska, Viktoriia V.; Стець, Олег Миколайович; Стець, О. М.; Стец, Олег Николаевич; Stets, Oleh M. (Riga : Izdevniecība “Baltija Publishing”, 2020)
The article is devoted to the study of the theoretical and legal foundations of the change of the vector of public administration, taking into account the humanistic tendencies of interaction of the subjects of public administration with the institutions of civil society. The features that characterize the subject of public administration are singled out: it is a somehow coordinated and organized system of bodies, which is not hierarchically structured, but should act in a coordinated, purposeful way, avoiding duplication of functions and excessive bureaucracy; the subject is the state, and the purpose of the subjects of public administration is to ensure the public interest – that is, the interests of both the state and society as a whole, rather than individual citizens and social groups; public administration relies on power, performing public functions; the activity of public administration extends to the whole society; public administration operates on the basis of a set of methods of influence: legal, political, economic, social through the use of methods of legal regulation, such as coordination, persuasion, incentives, coercion, etc. The basic international legal and national principles of involving citizens in public administration are analyzed. Emphasis is placed on the obligation of the state, represented by the authorized bodies, to create conditions for the real involvement of the public in the management of state and municipal affairs.

Стаття присвячена дослідженню теоретико-правових засад зміни вектора державного управління з урахуванням гуманістичних тенденцій взаємодії суб’єктів державного управління з інститутами громадянського суспільства. Виокремлено ознаки, що характеризують суб’єкт державного управління: це певним чином злагоджена й організована система органів, яка не має ієрархічної структури, але має діяти злагоджено, цілеспрямовано, уникаючи дублювання функцій та надмірного бюрократизму; суб'єктом є держава, а метою суб'єктів державного управління є забезпечення суспільних інтересів, тобто інтересів як держави, так і суспільства в цілому, а не окремих громадян і соціальних груп; державне управління спирається на владу, виконуючи державні функції; діяльність державного управління поширюється на все суспільство; державне управління функціонує на основі комплексу методів впливу: правового, політичного, економічного, соціального шляхом використання таких методів правового регулювання, як координація, переконання, стимулювання, примус тощо. Проаналізовано основні міжнародно-правові та національні принципи залучення громадян до державного управління. Акцентовано на обов’язку держави в особі уповноважених органів створити умови для реального залучення громадськості до управління державними та муніципальними справами.
Vasylkivska V. V. State of development of public administration in conditions of humanization tendencies / V. V. Vasylkivska, O. M. Stets // Public administration under modern conditions: concept, features, challenges : Collective monograph. - Riga : Izdevniecība “Baltija Publishing”, 2020. - P. 50-64.
Keywords: public administration; humanization tendencies; subject of public administration; involvement of the public; державне управління; тенденції гуманізації; суб'єкт державного управління; залучення громадськості; Research Subject Categories::LAW/JURISPRUDENCE::Public law::Administrative law